Pengaruh Kualitas Pelayanan, Harga, dan Lokasi Terhadap Keputusan Pembelian (Studi Kasus Pada Konsumen Stand Pakaian Pasar Tradisional Bandar Kediri) - Edy Djoko Soeprajitno (LPPM dan Fakultas Ekonomi dan Bisnis Universitas Kahuripan Kediri, 2018)
This research has objective (1) to analyze the influence of service quality to buying decision on consumer clothing stand of traditional market bandar kediri, (2) to analyze price influence to buying decision on consumer clothing stand of traditional market bandar Kediri, (3) To recognize the influence of location to buying decision at Consumer clothing Stand traditional market bandar Kediri, (4) Analyze the influence of service quality, price, and location to the buying decision on Consumer clothing stand traditional market bandar Kediri. Type This research is explanatory research by using quantitative approach. The sample in this research is consumer who shopping at stand of traditional market clothes of bandar kediri which amounted to 40 respondents with technique used is purposive sampling. Data collection techniques using questionnaires. The collected data is then analyzed using multiple linear regression simultaneously (F test) and partial (t test). The results showed that the quality of service, price and location simultaneously have a significant effect on consumer buying decisions at the traditional capital market clothing stand, this is indicated by the significance level of 0.001. Quality of service partially significant effect on consumer buying decisions at the stand of market clothes of traditional bandar kediri, this is indicated by the significance level of t test of 0.034. Price partially significant effect on consumer buying decision at stand of traditional market clothes of bandar kediri shown with level of significance equal to 0,031. While the location of partially significant effect on consumer buying decisions in the market dress stands of traditional bandar kediri, this is indicated by the significance level of t test of 0,030.